Development of protective schemes for hybrid AC/DC low-voltage distribution system. (February 2019) - Noh, Chul-Ho; Kim, Chul-Hwan; Gwon, Gi-Hyeon; Khan, Muhammad Omer; Jamali, Saeed Zaman
Highlights: Protection schemes based on interaction between LVDC and LVAC distribution system. Available normal operation even under fault condition of other system. A study based on transient analysis of a hybrid AC/DC LV distribution system. Introduction of reasonable criteria for setting values in the protection schemes. Abstract: As the interest in DC-based power system increases, the low-voltage DC (LVDC) distribution system is gaining attention. Until now, however, the related studies and developments are still not mature to commercialize the system. This corresponds to the protection system as well. In fact, previous studies have dealt with protection schemes targeting only the LVDC distribution system although the system is closely influenced by the low-voltage AC (LVAC) distribution system–hybrid AC/DC low-voltage (LV) distribution system. However, most literatures reporting the hybrid AC/DC LV distribution system do not focus on the protection scheme. Thus, in the work, the protective schemes for the hybrid AC/DC LV distribution system are developed and coordinated. The transient analysis on the events in both systems is first conducted; subsequently, the protection schemes for each system are developed. Finally, two proposed protection schemes are coordinated using the state diagram and their performances are verified through simulations using the electromagnetic transients program (EMTP).